Zona Norte : the post-structural body of erotic dancers and sex workers in Tijuana, San Diego and Los Angeles : an auto/ethnography of desire and addiction /: the post-structural body of erotic dancers and sex workers in Tijuana, San Diego and Los Angeles : an auto/ethnography of desire and addiction. (2009) - Unknown
No abstract available